2022
DOI: 10.3389/fpubh.2022.1044193
|View full text |Cite
|
Sign up to set email alerts
|

Global COVID-19 vaccine acceptance rate: Systematic review and meta-analysis

Abstract: BackgroundA vaccine against COVID-19 is a vital tool in managing the current pandemic. It is becoming evident that an effective vaccine would be required to control COVID-19. Effective use of vaccines is very important in controlling pandemics and paving the way for an acceptable exit strategy. Therefore, this systematic review and meta-analysis aims to determine the global COVID-19 acceptance rate that is necessary for better management of COVID-19 pandemic.MethodsThis review was conducted based on Preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
(100 reference statements)
3
13
0
Order By: Relevance
“…Our findings are consistent with a global systematic review that evaluated the vaccine acceptance rate among the general adult population as ranging from 63.9% to 68.55% [34–37]. However, the acceptance rate among PLHIV is considerably lower than the WHO target of 100%, in contrast to the rate for the general population (70%).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with a global systematic review that evaluated the vaccine acceptance rate among the general adult population as ranging from 63.9% to 68.55% [34–37]. However, the acceptance rate among PLHIV is considerably lower than the WHO target of 100%, in contrast to the rate for the general population (70%).…”
Section: Discussionsupporting
confidence: 88%
“…In a systematic review of the acceptance of the COVID-19 vaccine among adults, significant variations in vaccine acceptance among different countries were found [ 24 ]. Moreover, a recent systematic review reported that the global overall pooled acceptance rate of the COVID-19 vaccine was 64.9% [ 25 ]. In another systematic review of childhood COVID-19 vaccine hesitancy, higher vaccine hesitancy rates were documented in the USA and reached up to 86.1% and >85% in Saudi Arabia and Turkey [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses have been conducted in different countries regarding COVID-19 vaccine hesitancy [11][12][13][14][15][16]. Studies in Turkey have shown that COVID-19 vaccine hesitancy ranges from 2% to 98% [17,18].…”
Section: Introductionmentioning
confidence: 99%